1994
DOI: 10.1126/science.7915856
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Rate of Disease Development After HIV-2 Infection as Compared to HIV-1

Abstract: Human immunodeficiency virus type-2 (HIV-2) is a close relative of the prototype acquired immunodeficiency syndrome (AIDS) virus, HIV-1. HIV-2 is biologically similar to HIV-1, but information is lacking concerning clinical outcomes of HIV-2-infected individuals. From 1985 to 1993, a prospective clinical study was conducted in women with HIV-2 and HIV-1 infection to determine and compare rates of disease development. HIV-1-infected women had a 67% probability of AIDS-free survival 5 years after seroconversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
288
2
9

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(308 citation statements)
references
References 24 publications
9
288
2
9
Order By: Relevance
“…Individual patient numbers from Shankarappa et al [14] are shown in circles, and progression times for each patient are indicated in italics. doi:10.1371/journal.pcbi.0030029.g002 other hand, is known to be less transmissible and less pathogenic than HIV-1 group M [34,35]. The two HIV-1 group O datasets had dS rates that were similar to the rates estimated for HIV-1 subtype B moderate progressors (Table 2).…”
Section: Author Summarysupporting
confidence: 61%
See 1 more Smart Citation
“…Individual patient numbers from Shankarappa et al [14] are shown in circles, and progression times for each patient are indicated in italics. doi:10.1371/journal.pcbi.0030029.g002 other hand, is known to be less transmissible and less pathogenic than HIV-1 group M [34,35]. The two HIV-1 group O datasets had dS rates that were similar to the rates estimated for HIV-1 subtype B moderate progressors (Table 2).…”
Section: Author Summarysupporting
confidence: 61%
“…Therefore, these findings seem to resolve the longstanding issue of the nonpathogenic nature of SIV infection. In addition, it provides an explanation for the lower pathogenicity of HIV-2 infections [35] and the generally low HIV-2 synonymous substitution rates observed in this study. Nef-mediated TCR-CD3 down-modulation also correlated with CD4þ T cell depletion in SIVsmm infected sooty mangabeys [45].…”
Section: Discussionmentioning
confidence: 88%
“…Some studies have reported that disease progression is more rapid in Africa (1-3), but others contest this view (4,5). In Uganda, a study has demonstrated that the time from seroconversion to death is very similar to that reported for patients in industrialized countries prior to the introduction of anti-retroviral therapy (6).…”
mentioning
confidence: 71%
“…Thus, HIV-2 is characterized by higher CD4 counts, low level of viremia, and low transmission rate. 54 It has been reported that the low pathogenicity of HIV-2 is associated with a lower immune activation and a lesser degree of CD4 T-cell apoptosis. 55 Importantly, the magnitude of CD4 þ T-cell apoptosis observed in HIV-infected individuals correlates well with the stage of HIV disease.…”
Section: T-cell Apoptosis and Aidsmentioning
confidence: 99%